Recommendations for improving clinical trial design to facilitate the study of youth-onset type 2 diabetes - DEMİRCİOĞLU, SERAP (SAGE PUBLICATIONS LTD, 2020)
Background The prevalence of type 2 diabetes is increasing in youths and differs from adult-onset type 2 diabetes in its characteristics and progression. Currently, only two drugs are approved for youth-onset type 2 diabetes and many patients are not meeting glycemic targets. Clearly, there is an urgent need to complete clinical trials in youths with type 2 diabetes to increase the therapeutic choice for these patients. However, factors such as limited patient numbers, unwillingness of patients to participate in trials, failure to meet strict inclusion and exclusion criteria, and poor clinic attendance have limited the size and number of trials in this complicated patient demographic. Recommendations This is a narrative opinion piece on the design of clinical trials in youth-onset type 2 diabetes prepared by researchers who undertake this type of study in different countries. The review addresses possible ways to enhance trial designs in youth-onset type 2 diabetes to meet regulatory requirements, while minimizing the barriers to patients' participation. The definition of adolescence, recruitment of sufficient patient numbers, increasing flexibility in selection criteria, improving convenience of trial visits, requirements of a control group, possible endpoints, and trial compliance are all considered. The authors recommend allowing extrapolation from adult data, using multiple interventional arms within future trials, broadening inclusion criteria, and focusing on endpoints beyond glucose control, among others, in order to improve the successful completion of more trials in this population. Conclusions Improvements in trial design will enable better recruitment and retention and thereby more evidence for treatment outcomes for youth-onset type 2 diabetes.
Keywords: Adolescent; clinical trials as topic; diabetes mellitus; type 2; therapy; health services needs and demand; hypoglycemic agents; therapeutic use; CARDIOVASCULAR OUTCOMES; SOCIAL DETERMINANTS; PEDIATRIC-PATIENTS; TREATMENT OPTIONS; GLYCEMIC CONTROL; GLUCOSE CONTROL; SINGLE-BLIND; ADOLESCENTS; CHILDREN; METFORMIN